Comparing HIV risk-related behaviors between 2 RDS national samples of MSM in Brazil, 2009 and 2016. (May 2018) - Guimarães, Mark Drew Crosland; Kendall, Carl; Magno, Laio; Rocha, Gustavo Machado; Knauth, Daniela Riva; Leal, Andrea Fachel; Dourado, Ines; Veras, Maria Amélia; Brito, Ana Maria de; Kerr, Ligia Regina Franco Sansigolo
Abstract: Introduction: Periodic monitoring of sociobehavior characteristics at a national level is an essential component of understanding the dynamics the human immunodeficiency virus (HIV) epidemic worldwide, including Brazil. Methods: This paper compares descriptive sociobehavior characteristics in 2 national cross-sectional HIV biological behavioral surveillance surveys (BBSS) conducted in 2009 and 2016 among men who have sex with men (MSM) in Brazil. Respondent driven sampling (RDS) was used for recruitment in both years. Overall proportions were weighted according to Gile's estimator using RDS Analyst Software and 95% confidence intervals were calculated for comparisons between the 2 periods. Further comparisons were stratified by age groups (<25 and 25+ years old). Results: Overall, 3749 and 4176 MSM were recruited in 2009 and 2016, respectively. In 2016, participants were younger than 25 years old (58.3%), with 12 or more years of education (70.4%), with higher socioeconomic status (40.7%), and had a higher proportion of whites (31.8%), as compared to 2009. Also, participants in 2016 reported less alcohol use and binge drinking, but used illicit drugs more frequently. There was an increase among MSM who self-reported their HIV risk as low and had low HIV knowledge while the proportion of those who were never tested for HIV dropped from 49.8% in 2009 to 33.8% in 2016. Although more than three-quarters received free condoms in both years, STD counseling remained low (32% and 38% for 2009 and 2016, respectively). Sexual risk behavior remained at high levels, especially unprotected anal receptive sex and sex with multiple partners. Younger MSM (<25 years old) showed riskier sexual practices than those 25+ years old, when comparing 2016 to 2009. Conclusions: Our results indicate a worrisome risk behavior trend among Brazilian MSM, especially among younger ones. These results can contribute for a better understanding of the HIV epidemics in Brazil, with timely shift in strategies so improved effectiveness in public health prevention efforts can be achieved.